Enhanced cellular uptake and tumor penetration of nanoparticles by imprinting the "hidden" part of membrane receptors for targeted drug delivery. Issue 81 (20th September 2017) - Peng, Shan; Wang, Yahua; Li, Na; Li, Chong
Abstract : Biting deep into the target cell membrane: nanoparticles targeting the transmembrane domain by trifluoroethanol-assisted epitope imprinting. Abstract : The widely existing transmembrane helices can serve as a novel type of binding site for recognizing corresponding membrane receptors. Through imprinting the transmembrane domain of certain receptors, here we report the construction of polymeric nanoparticles which can achieve enhanced cellular uptake and permeability in target tissues for tumor-targeted drug delivery.